HUBUNGAN KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DENGAN KARAKTER GOTONG ROYONG DI SEKOLAH DASAR - Windiatmoko, Akmal Irfan; Farida Nugrahani; Meidawati Suswandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Implementing the Project for Strengthening the Profile of Pancasila Students requires loyalty between students and groups as a form of solidarity. This is a form of strengthening the Pancasila Student Profile dimension of mutual cooperation. So the aim of this research is to describe the relationship between the activities of the Project for Strengthening Pancasila Student Profiles and the Character of Mutual Cooperation. This research is a correlational quantitative research. In this research, data was collected using a questionnaire with a Likert scale and the data processed was ordinal data so that the analysis used was non-parametric statistics. Hypothesis testing uses Spearman's rho Rank Correlation Test. with a high class sample of 20 students at SDN 02 Menjing, Jenawi District, Karanganyar Regency. It is known from the research results that the calculated p shows 0.691 which has a p calculated correlation strength between 0.600 to 0.799 with a strong category. If seen from the sig value and the value level it is smaller than the significant value of 0.05, namely 0.001 or the calculated p and p table, namely 0.691>0.444. Thus p calculates p table, then Ho is rejected and Ha is accepted.